Elevating larval source management as a key strategy for controlling malaria and other vector-borne diseases in Africa - Fredros Okumu; Sarah J. Moore; Prashanth Selvaraj; Arnon Houri Yafin; Elijah O. Juma; GloriaSalome G. Shirima; Silas Majambere; Andy Hardy; Bart G. J. Knols; Betwel J. Msugupakulya; Marceline Finda; Najat Kahamba; et al. (Parasites & Vectors)
Abstract Larval source management (LSM) has a long history of advocacy and successes but is rarely adopted where funds are limited. The World Health Organization (WHO) guidelines on malaria prevention recommend the use of LSM as a supplementary intervention to the core vector control methods (insecticide-treated nets and indoor residual spraying), arguing that its feasibility in many settings can be limited by larval habitats being numerous, transient, and difficult to find or treat. Another key argument is that there is insufficient high-quality evidence for its effectiveness to support wide-scale implementation. However, the stagnation of progress towards malaria elimination demands that we consider additional options to the current emphasis on insecticidal commodities targeting adult mosquitoes inside homes. This letter is the result of a global, crossdisciplinary collaboration comprising: (a) detailed online expert discussions, (b) a narrative review of countries that have eliminated local malaria transmission, and (c) a mathematical modeling exercise using two different approaches. Together, these efforts culminated in seven key recommendations for elevating larval source management as a strategy for controlling malaria and other mosquito-borne diseases in Africa (Box 1). LSM encompasses the use of larvicide (a commodity) as well as various environmental sanitation measures. Together, these efforts lead to the long-term reduction of mosquito populations, which benefits the entire community by controlling both disease vector and nuisance mosquitoes. In this paper, we argue that the heavy reliance on large-scale cluster-randomized controlled trials (CRTs) to generate evidence on epidemiological endpoints restricts the recommendation of approaches to only those interventions that can be measured by functional units and deliver relatively uniform impact and, therefore, are more likely to receive financial support for conducting these trials. The explicit impacts of LSM may be better captured by using alternative evaluation approaches, especially high-quality operational data and a recognition of locally distinct outcomes and tailored strategies. LSM contributions are also evidenced by the widespread use of LSM strategies in nearly all countries that have successfully achieved malaria elimination. Two modelling approaches demonstrate that a multifaceted strategy, which incorporates LSM as a central intervention alongside other vector control methods, can effectively mitigate key biological threats such as insecticide resistance and outdoor biting, leading to substantial reductions in malaria cases in representative African settings. This argument is extended to show that the available evidence is sufficient to establish the link between LSM approaches and reduced disease transmission of mosquito-borne illnesses. What is needed now is a significant boost in the financial resources and public health administration structures necessary to train, employ and deploy local-level workforces tasked with suppressing mosquito populations in scientifically driven and ecologically sensitive ways. In conclusion, having WHO guidelines that recognize LSM as a key intervention to be delivered in multiple contextualized forms would open the door to increased flexibility for funding and aid countries in implementing the strategies that they deem appropriate. Financially supporting the scale-up of LSM with high-quality operations monitoring for vector control in combination with other core tools can facilitate better health. The global health community should reconsider how evidence and funding are used to support LSM initiatives. Graphical Abstract